2016
DOI: 10.1111/1758-2229.12430
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of the sponge microbiome favors tolerance to ocean acidification

Abstract: Ocean acidification is increasing and affects many marine organisms. However, certain sponge species can withstand low-pH conditions. This may be related to their complex association with microbes. We hypothesized that species with greater microbial diversity may develop functional redundancy that could enable the holobiont to survive even if particular microbes are lost at low-pH conditions. We evaluated the effects of acidification on the growth and associated microbes of three ubiquitous Mediterranean spong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 39 publications
6
53
0
Order By: Relevance
“…Sponge symbionts exhibit resistance mechanisms designed to specifically address changes in host conditions that generally lead to stress. In this context, genomic studies of sponge‐associated microbial communities have revealed an enrichment of stress‐related proteins (López‐Legentil et al ., ; Fan et al ., ; Liu et al ., ) that may help symbionts cope with environmental stressors, including the presence of antimicrobial compounds (Piel, ), bioaccumulation of heavy metals (Hansen et al ., ; Webster et al ., ), and changes in temperature (Fan et al ., ), pH (Ribes et al ., ) and sedimentation (Luter et al ., ). The SAUL clade possesses genomic signatures related to adaptation to the microenvironment of the host sponge, with both bins carrying genes encoding proteins such as UspA (universal stress protein A) (annotated as COG0589), which is synthesised in response to environmental stress such as heat and/or osmotic shock, nutrient starvation, or exposure to heavy metals (Nyström and Neidhardt, ; Kvint et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Sponge symbionts exhibit resistance mechanisms designed to specifically address changes in host conditions that generally lead to stress. In this context, genomic studies of sponge‐associated microbial communities have revealed an enrichment of stress‐related proteins (López‐Legentil et al ., ; Fan et al ., ; Liu et al ., ) that may help symbionts cope with environmental stressors, including the presence of antimicrobial compounds (Piel, ), bioaccumulation of heavy metals (Hansen et al ., ; Webster et al ., ), and changes in temperature (Fan et al ., ), pH (Ribes et al ., ) and sedimentation (Luter et al ., ). The SAUL clade possesses genomic signatures related to adaptation to the microenvironment of the host sponge, with both bins carrying genes encoding proteins such as UspA (universal stress protein A) (annotated as COG0589), which is synthesised in response to environmental stress such as heat and/or osmotic shock, nutrient starvation, or exposure to heavy metals (Nyström and Neidhardt, ; Kvint et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…During our chamber experiments, pH was not measured and any impacts of lowered pH on the tested sponge holobionts remain unknown. However, previous work indicated that the microbiome of Mediterranean sponges was relatively stable in terms of abundance, richness, and diversity under comparable pH shifts (> 60 d at a pH ≈ 7.8; Ribes et al ). The impact of this pH shift on the metabolic function of the microbiome is unknown, but we posit the brevity of the exposure to a large magnitude shift will temper any impact.…”
Section: Methodsmentioning
confidence: 94%
“…Most recently, microbial symbionts of tropical sponges were shown to produce and store polyphosphate granules (Zhang et al, 2015), perhaps enabling the host to survive periods of phosphate depletion in oligotrophic marine environments (Colman, 2015). The microbiomes of some sponge species do appear to change in community structure in response to changing environmental conditions, including temperature (Simister et al, 2012a) and ocean acidification (Morrow et al, 2015;Ribes et al, 2016), as well as synergistic impacts (Lesser et al, 2016). Understanding the effect of these altered host-microbiome interactions on sponge growth and ecology are topics for further research.…”
Section: Overview Of Diverse and Emerging Animal-microbiome Study Sysmentioning
confidence: 99%